2001
DOI: 10.1111/j.1600-0463.2001.tb05781.x
|View full text |Cite
|
Sign up to set email alerts
|

Trends in incidence of testicular cancer and prostate cancer in Denmark

Abstract: This article presents a detailed analysis of the incidence trends of testicular cancer and prostate cancer, using information from the Danish Cancer Registry in the period 1943–1996. The rate of increase of testicular cancer was about 2.6% per year. The analyses indicated that incidence was more strongly dependent on the man's birth cohort than on the calendar period. The analysis confirmed the significantly reduced incidence of testicular cancer in the 1943 cohort and suggested a levelling off in the increase… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

7
24
0

Year Published

2002
2002
2017
2017

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(31 citation statements)
references
References 21 publications
7
24
0
Order By: Relevance
“…A previous Danish study based on nationwide registry data from the period 1943–1996 found that the incidence of prostate cancer increased about 1.6% per year 20. It was concluded that the epidemiological pattern of prostate cancer incidence seemed to be dominated by changes in diagnosis and registration rather than changes in causal factors, which supports our speculation concerning the current results.…”
Section: Discussionsupporting
confidence: 88%
“…A previous Danish study based on nationwide registry data from the period 1943–1996 found that the incidence of prostate cancer increased about 1.6% per year 20. It was concluded that the epidemiological pattern of prostate cancer incidence seemed to be dominated by changes in diagnosis and registration rather than changes in causal factors, which supports our speculation concerning the current results.…”
Section: Discussionsupporting
confidence: 88%
“…Over the last few decades, a marked increase in the incidence of testicular cancer has been well documented in the cancer registries of many countries 1, 2. A particular feature of testicular cancer is that the vast majority of tumours originate from germ cells.…”
Section: Introductionmentioning
confidence: 99%
“…Both conditions are related to and are known to be risk factors for the development of low sperm count and testicular cancer in adult life 5. Recent data from large, longitudinal population studies carried out in Denmark and Finland report the prevalence of cryptorchidism at birth of 8.2% and 2.2%, respectively 2.…”
mentioning
confidence: 99%